Abnormal cementing prevention material for well cementing slurry as well as preparation method and application of abnormal cementing prevention material
By using cementing cementing cementing slurry anti-anomaly gelling materials of sodium boron calcite, slab calcite, silosilicate and cyst in 10,000-meter deep well exploration, combined with hydrolysis reaction and coating treatment, abnormal cementing slurry was solved at high temperatures. The problem of this has achieved the improvement of the stability of thickening performance and construction safety.
Patent Information
- Application Number
- CN202411402911.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-09
AI Technical Summary
During the exploration and development of 10,000-meter deep wells, oil well cement is prone to abnormal gelation in high temperature environments, affecting the safety of cementing construction. The existing technology is difficult to effectively adapt to the fluctuations in different batches of cement mineral components and polymer polymer complex glues. Condensation effect.
A cementing cement slurry anti-abnormal gelling material, including sodium boron calcite, slab calcite, silosilicate and cystylite, release sulfate ions and copper ions through hydrolysis, preventing rapid hydration of tricalcite aluminate , and the hydrolysis reaction of sulfate components is prevented by coating treatment to ensure stable thickening performance of cement slurry.
It effectively inhibits the abnormal gelation phenomenon of cement slurry, adapts to changes in cement mineral components in different batches, ensures the stability of the thickening performance of cement slurry at high temperatures, improves the density and compressive strength of cement stone, and ensures the cementing construction. Security.
Smart Images

Figure CN119241123A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cementing materials for oil and gas well engineering, and more specifically to a cementing slurry abnormal gelling prevention material and a preparation method and application thereof. Background Art
[0002] 39% of the remaining oil and 57% of the remaining natural gas on land in my country are distributed in deep reservoirs. The ultra-deep oil and gas resources of 10,000 meters have become an important area for increasing reserves and production of my country's oil and gas reservoirs. In the process of oil and gas well exploitation, cementing is a key engineering technology to ensure safe production throughout the life cycle of the wellbore and achieve efficient development. Due to the high temperature working environment underground, especially when the temperature exceeds 180°C, the hydration and hardening process of oil well cement, the composition of hydration products, and the performance of retarders will all change significantly, which can easily affect the stability of cement slurry thickening performance, mainly manifested in the abnormal gelation phenomenon that is easy to cause during the slurry heating process, and the thickening time is difficult to adjust linearly. Abnormal gelation of cement slurry will greatly affect the safety of cementing construction. Therefore, it is urgent to solve this technical problem during the exploration and development of 10,000-meter deep wells.
[0003] The existing technical means mainly optimize the composition of fluid loss reducer and retarder. For example, the invention patent application publication text with the application publication date of July 29, 2022, the application publication number of CN114805706A, and the name of "A fluid loss reducer for inhibiting early abnormal gelation of cement slurry and its preparation method" specifically discloses that the fluid loss reducer is a tetrapolymer, comprising 55-70 parts of component A, 10-15 parts of component B, 10-15 parts of component C, and 10-15 parts of component D, A is AMPS or AMPS salt, component B is acrylamide, component C is tannin, and component D is nitrogen-substituted acrylamide. Its synthetic product has good performance in inhibiting early abnormal gelation of cement slurry, and also has the basic performance required by fluid loss reducer such as reducing water loss and adjusting cement slurry rheology.
[0004] For example, the application publication date is April 18, 2022, the application publication number is CN114292634A, and the invention patent application publication text named "A multi-stage adsorption polymer fluid loss reducer and its preparation method" specifically discloses that the multi-stage adsorption polymer fluid loss reducer is composed of 35% to 60% of binary copolymer, 20% to 40% of ternary copolymer and 10% to 30% of tetrapolymer. Its synthetic product can be used for ultra-high temperature deep well cementing, and the applicable temperature can reach 30℃ to 210℃. It can effectively inhibit the transition dispersion under high temperature and cause the cement slurry to deteriorate in stability, and improve the situation where too many strong adsorption groups cause abnormal gelation of cement slurry.
[0005] For example, the invention patent application publication text, whose application publication date is September 15, 2020, and whose application publication number is CN111662409A, and whose name is “A high-temperature oil well cement retarder capable of inhibiting abnormal gelation and preparation method thereof”, specifically discloses that its preparation method includes: (1) dissolving 2-acrylamide-2-methylpropanesulfonic acid and unsaturated carboxylic acid monomers in deionized water, stirring evenly, and adjusting the pH to 5-6; (2) adding steric hindrance functional monomers and cationic functional monomers to the solution obtained in step (1), stirring evenly, and heating to 55-65°C; (3) dissolving an initiator in deionized water to form a solution, adding the solution to the solution obtained in step (2) under stirring, keeping the solution at 55-65°C for 20-40 minutes, heating the solution to 70-85°C and reacting at a constant temperature for 2-4 hours to obtain a high-temperature oil well cement retarder capable of inhibiting abnormal gelation. The synthetic product can inhibit the "bulging" and "coring" phenomena of cement slurry in the temperature range of 120-150°C, and does not affect the strength development of cement stone. The comprehensive performance of cement slurry is good.
[0006] For another example, the invention patent application publication text, entitled "A medium-high temperature oil well cement retarder, its preparation method and application", with application publication date of March 22, 2019 and application publication number of CN109503760A, specifically discloses that itaconic acid, acrylic acid and 2-acrylamido-2-methylpropanesulfonic acid are polymerized in water in the presence of organic phosphonates and initiators to obtain a medium-high temperature oil well cement retarder. The synthetic product is a medium-high temperature oil well cement retarder with an applicable temperature range of 65 to 135°C. It overcomes the sensitivity of small molecule compound addition, the high initial consistency of carboxylic acid polymers and abnormal gelation, and there is no inversion phenomenon when used.
[0007] The above technical means mainly optimize the organic macromolecular structure of polymers, ignoring the influence of cement matrix mineral components and batch composition fluctuations, resulting in the difficulty of admixtures to effectively adapt to different batches of cement slurry systems. Therefore, in solving the problem of abnormal gelation of cement slurry, it is necessary to solve the complex gelation effect of polymer macromolecules on cement hydration products, and to effectively inhibit abnormal gelation of slurry when the mineral components of cement matrix fluctuate, so as to ensure the stable control of the thickening performance of ultra-high temperature cement slurry system. Summary of the invention
[0008] In order to overcome the defects and deficiencies in the above-mentioned prior art, the present invention provides a cementing slurry anti-abnormal gelling material and its preparation method and application. The purpose of the present invention is to solve the complex gelling effect of polymer macromolecules on cement hydration products, and to solve the problem of inhibiting abnormal gelling of slurry when the mineral composition of cement substrate fluctuates. The anti-abnormal gelling material for cementing slurry for ultra-deep wells of 10,000 meters of the present invention is an inorganic material, which can not only ensure stable performance without failure in ultra-high temperature environment, but also has good compatibility with cement substrate, high-temperature admixture and additive, and has a wide range of applications.
[0009] In order to solve the above problems existing in the prior art, the present invention is implemented through the following technical solutions.
[0010] The first aspect of the present invention provides a cementing slurry abnormal gelling prevention material, comprising the following components in parts by weight: 40-60 parts of ulexite; 20-40 parts of colemanite; 10-20 parts of pyrophyllite; 5-15 parts of gallstones; The chemical composition requirements of the abnormal gelling material for cementing slurry are: 37wt.%<B2O3≤55wt.%, 11wt.%<CaO≤21wt.%, 5wt.%<SiO2≤13wt.%, 6wt.%<Na2O≤12wt.%, 1wt.%<SO3≤6wt.%, 1wt.%<CuO≤6wt.%; The particle fineness requirements of the abnormal gelling prevention material of the cementing slurry are Dx(10)≤5μm, Dx(50)≤14μm, and Dx(90)≤30μm.
[0011] Further preferably, the purity of the ulexite is required to be ≥90wt.%, and its chemical composition requirements are: Na2O>6wt.%, CaO>12wt.%, B2O3>38wt.%.
[0012] Further preferably, the purity of the colemanite is required to be ≥90wt.%, and its chemical composition requirements are: CaO>18wt.%, B2O3>33wt.%.
[0013] Further preferably, the purity of the nautilus stone is required to be ≥90wt.%, and its chemical composition requirements are: Na2O>22wt.%, SiO2>42wt.%, B2O3>24wt.%.
[0014] Further preferably, the purity of the gallstone is required to be ≥90wt.%, and its chemical composition requirements are: CuO>28wt.%, SO3>28wt.%.
[0015] A second aspect of the present invention provides a method for preparing a cementing slurry abnormal gelling prevention material, comprising the following steps: S1. Mix 40-60 parts of ulexite, 20-40 parts of colemanite and 10-20 parts of boraxite evenly, crush them after mixing evenly, and control the crushing ratio to 40-70; grind the crushed mixed material into mixed fine material, and control the crushing ratio to 400-900; send the crushed mixed fine material to a high-temperature calcining furnace for calcination, and control the calcination temperature to 800°C-1500°C; the mixed material after calcination is quickly cooled to room temperature, and the cooling time is controlled to 10-20min; after cooling, obtain Class A mixed material; S2, mixing the Class A mixture prepared in step S1 with 5-15 parts of gallstones, and grinding the mixture to obtain a Class B mixture; the particle size requirements of the Class B mixture are Dx(10)≤5μm, Dx(50)≤14μm, and Dx(90)≤30μm; S3, subjecting the Class B mixture to a coating treatment, specifically, adding the Class B mixture to a coating solution, mixing evenly and reacting for a set time, and vacuum drying to obtain the cement slurry anti-abnormal gelling material.
[0016] Further preferably, the coating solution comprises the following components by mass ratio: Anhydrous ethanol: phenolic resin: polymethyl methacrylate: dimethyl phthalate: diethyl phthalate = (55~70): (15~25): (5~10): (5~10): (5~10).
[0017] More preferably, the concentration of the plating solution is 55 wt.% to 85 wt.%.
[0018] More preferably, in step S3, the usage ratio of the type B mixture to the plating solution is 1:(5-20).
[0019] More preferably, in step S3, the reaction time is set to 5 to 35 minutes.
[0020] More preferably, in step S3, the vacuum drying temperature is 35°C to 55°C.
[0021] A third aspect of the present invention provides an application of an abnormally gelling material for cementing slurry in cementing slurry for ultra-deep wells of 10,000 meters.
[0022] Compared with the prior art, the beneficial technical effects brought by the present invention are as follows: 1. The abnormal gelling prevention material for cementing slurry of the present invention can be applied to cementing slurry for ultra-deep wells of 10,000 meters, and can inhibit abnormal gelling of cementing slurry for ultra-deep wells of 10,000 meters. The abnormal gelling prevention material for cementing slurry of the present invention is based on the perspective of cement hydration products to solve the abnormal gelling effect of cement slurry caused by fluctuations in cement mineral components in different batches.
[0023] The solution is as follows: different batches of cement have different tricalcium aluminate contents in their mineral components, and thus different aluminum ion contents in the cement slurry. Tricalcium aluminate hydrates very quickly, quickly forming hydrated calcium aluminate gel products in the cement slurry, causing abnormal gelation phenomena such as thickening of the cement slurry. In addition, when the aluminum ion concentration in the cement slurry reaches a certain level, it will combine and cross-link with the calcium ions and the polymer chains in the polymer admixture to form a mutually doped cross-linked network structure, causing abnormal gelation of the cement slurry (the thickening curve shows "bulging" and "core-encapsulation" phenomena). The abnormal gelling prevention material for cementing slurry of the present invention releases sulfate ions through hydrolysis reaction, and reacts with aluminum ions and calcium ions under medium-high temperature hydrothermal conditions to generate monosulfur calcium sulfoaluminate. On the one hand, the aluminum ion content in the cement slurry is reduced, and aluminum ions are prevented from forming a mutually doped cross-linked network structure with other ions and high molecular chains in the polymer admixture; on the other hand, the monosulfur calcium sulfoaluminate is wrapped on the surface of tricalcium aluminate to prevent its rapid hydration, thereby preventing the rapid formation of hydrated calcium aluminate in the cement slurry, thereby preventing the cement slurry from abnormal gelling.
[0024] Therefore, no matter how the cement batches and their mineral components change, the main difference is the aluminum phase content in the cement components. The present technical means solves the abnormal gelling effect of aluminum ions on cement slurry from the root, so that the anti-abnormal gelling material of the present invention can adapt to different batches of cement.
[0025] 2. The anti-abnormal gelling material for cementing slurry of the present invention can effectively inhibit the problem of abnormal gelling caused by complexation between admixtures and cement components. The working principle is as follows: high-temperature cementing slurry systems usually use polymer admixtures. The macromolecules in the admixtures compete for calcium ions in the cement slurry, and usually multiple polymer molecules chelate one calcium ion, thereby causing the long-chain macromolecules to form a bridge network, resulting in abnormal gelling of the cement slurry. The anti-abnormal gelling material for cementing slurry of the present invention releases borate ions and copper ions through a hydrolysis reaction. On the one hand, the copper ions will deprive the chelated calcium ions in the polymer molecules. Since the relative atomic mass of the copper ions is larger than that of the calcium ions, the copper ions will sink with the chelated polymer molecules in the cement slurry, thereby separating multiple polymer molecules. On the other hand, the borate ions will also rob the chelated calcium ions in the polymer molecules and preferentially form calcium borate. The calcium borate is quickly wrapped on the surface of tricalcium silicate and dicalcium silicate to prevent them from undergoing a hydration reaction, thereby prolonging the thickening time of the cement slurry. At this time, the deprived polymer molecules are uniformly dispersed in the cement slurry in a flowing state, thereby inhibiting the high molecular long-chain polymer from forming a bridge network, thereby preventing the cement slurry from undergoing abnormal gelling.
[0026] 3. In the present invention, the chemical composition of the material for preventing abnormal gelling of cement slurry is limited. Only the gelling material that meets the chemical composition can ensure the performance of the material for preventing abnormal gelling of cement slurry. The chemical composition is a ratio of chemical components specifically for the abnormal gelling phenomenon of cement slurry. Each component can exert the best performance of the material within this limited range.
[0027] 4. The present invention further limits the particle size of the material for preventing abnormal gelling of cement slurry. If the material is too fine, it will affect the compatibility of the material with other materials, for example, forming abnormal gelling or performance conflicts with other materials. In addition, if the material is too fine, its solubility will be accelerated, and water absorption too quickly will easily cause the cement slurry to thicken, which is not conducive to construction safety. ② If the material is too coarse, its solubility will deteriorate, and the performance of the material cannot be exerted in time. In addition, if the material is too coarse, it will also settle, thereby affecting the stability of the material. Therefore, as long as the particle fineness requirement exceeds this range, the best performance of the material cannot be exerted, so it is necessary to limit the fineness of the material of this application.
[0028] 5. The anti-abnormal gelling material for cementing slurry of the present invention is an inorganic material, which has no negative impact on the engineering performance of cement slurry and the mechanical properties of cement stone. It can not only ensure stable performance without failure in ultra-high temperature environment, but also has good compatibility with cement substrate, high-temperature admixture and admixture. In addition, the anti-abnormal gelling material of the present invention contains part of tricalcium silicate and dicalcium silicate. When the cement slurry solidifies to form cement stone, the residual tricalcium silicate and dicalcium silicate in the anti-abnormal gelling material will fill in the pores of cement stone and slowly undergo hydration reaction. The formed hydrated calcium silicate gel will continuously fill the tiny pores in cement stone, thereby improving the density of cement stone, which has a beneficial effect on the compressive strength of cement stone at high temperature.
[0029] 6. The present invention further defines the purity and chemical composition requirements of each component. By further defining and optimizing the purity and chemical composition of each component, it can ensure that the cementing slurry anti-abnormal gelling material obtained after compounding the components can meet the chemical composition requirements and achieve the best performance of the material. And the further definition of the purity and chemical composition requirements of each component can improve the compounding success rate of the cementing slurry anti-abnormal gelling material, so that the material obtained after compounding the components can meet its chemical composition requirements and achieve the best performance of the material.
[0030] 7. When preparing the fixed cement slurry to prevent abnormal gelling material, the Class B mixture is subjected to coating treatment. The purpose is: the sulfate component in the Class B mixture will undergo a hydrolysis reaction during the cement slurry preparation process, and the released sulfate ions will react with the aluminum ions and calcium ions in the cement slurry to form ettringite. Under low temperature conditions (generally below 70°C), ettringite is relatively stable. A large amount of water will be consumed in the process of its formation. At the same time, the needle-shaped ettringite is interspersed and intertwined with each other, which can easily cause the cement slurry to thicken rapidly in a short period of time (mainly manifested in the "bulging" phenomenon on the cementing cement slurry thickening curve), seriously affecting the safety of cementing construction. Therefore, a coating method is adopted to form a layer of plastic resin protective film on the surface of Class B mixture particles. Under low temperature conditions, it can effectively prevent the sulfate component in Class B mixture from reacting with water, reduce the concentration of sulfate ions in the cement slurry, and thus prevent the formation of calcium sulfonate. At this time, Class B mixture is evenly dispersed in the cement slurry as a filling material. As the temperature rises during the grouting process, the resin protective film begins to decompose (generally above 70°C), and Class B mixture begins to hydrolyze. Although the sulfate ion concentration in the cement slurry will increase at this time, the generated calcium sulfonate is extremely unstable in medium and high temperature environments and will decompose rapidly, which will not cause the cementing cement slurry to thicken rapidly, thereby ensuring the smooth progress of cementing construction.
[0031] 8. The coating solution used in the preparation of the anti-abnormal gelling material for cementing slurry in the present invention can be selected from existing commonly used coating solutions, as long as a plastic resin protective film can be formed on the surface of the Class B mixed material particles, and the resin protective film can be decomposed above 70°C. As a preferred embodiment of the present invention, the coating solution used in the present invention includes anhydrous ethanol, phenolic resin, polymethyl methacrylate, dimethyl phthalate and diethyl phthalate compounded according to a set ratio, and its constituent monomers and ratios are optimal. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a graph showing the thickening curve test results of the S1# cement slurry system provided in Example 1 of the present invention; Figure 2 This is a graph showing the thickening curve test results of the D1# cement slurry system provided in Comparative Example 1 of the present invention; Figure 3 This is a graph showing the thickening curve test results of the S2# cement slurry system provided in Example 2 of the present invention; Figure 4 This is a graph showing the thickening curve test results of the D2# cement slurry system provided in Comparative Example 2 of the present invention; Figure 5 This is a graph showing the thickening curve test results of the S3# cement slurry system provided in Example 3 of the present invention; Figure 6 This is a graph showing the thickening curve test results of the D3# cement slurry system provided in Comparative Example 3 of the present invention; Figure 7 This is a graph showing the thickening curve test results of the S4# cement slurry system provided in Example 4 of the present invention; Figure 8 This is a graph showing the thickening curve test results of the D4# cement slurry system provided in Comparative Example 4 of the present invention; Fig. 9 This is a graph showing the thickening curve test results of the S5# cement slurry system provided in Example 5 of the present invention; Fig.10 This is a graph showing the thickening curve test results of the D5# cement slurry system provided in Comparative Example 5 of the present invention. DETAILED DESCRIPTION
[0033] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The following examples are all prepared in accordance with GB / T 19139-2012 standard. In the cement slurry system listed in the examples, the cement used is Jiahua G-grade high-resistance cement, quartz sand and metakaolin can be purchased from the market, the high-temperature stabilizer is a mixture of ultrafine materials and clay substances, the high-temperature fluid loss reducer is AMPS-VP-AM-AA tetrapolymer, and the high-temperature retarder is AMPS-itaconic acid copolymer.
[0035] Example 1 As a preferred embodiment of the present invention, this embodiment discloses a cementing slurry anti-abnormal gelling material, which includes the following components by weight: 60 parts of ulexite, 25 parts of colemanite, 10 parts of ulexite and 5 parts of chalcanthite.
[0036] In this embodiment, the above-mentioned cement slurry abnormal gelling prevention material is prepared by the following preparation method: S1. 60 parts by weight of ulexite, 25 parts by weight of colemanite and 10 parts by weight of boraxite are uniformly mixed, and then crushed by a grinding mill, with the crushing ratio controlled at 60; the crushed mixed material is sent to a ball mill for grinding into a mixed fine material, with the crushing ratio controlled at 700; then the crushed mixed fine material is sent to a high-temperature calcining furnace for calcining, with the calcining temperature controlled at 1350°C, and the mixed material after calcination is quickly cooled to room temperature by a cooler, and the cooling time is controlled at 20min to obtain a Class A mixed material.
[0037] S2. Mix the Class A mixture prepared in step S1 with 5 parts by weight of gallstones and send it to a ball mill for grinding. After grinding, a Class B mixture is obtained; the particle size requirements of the Class B mixture are Dx(10)≤5μm, Dx(50)≤14μm, and Dx(90)≤30μm.
[0038] S3. The Class B mixture is subjected to coating treatment, specifically, 100 parts by weight of the Class B mixture is added to 500 parts by weight of a coating solution having a concentration of 80 wt.%, mixed evenly and reacted for 5 minutes, and then placed in a 35°C vacuum drying oven for drying to obtain the cement slurry anti-abnormal gelling material, referred to as "S1# material".
[0039] The chemical composition requirements of the above-mentioned "S1# material" are: 37wt.%<B2O3≤55wt.%, 11wt.%<CaO≤21wt.%, 5wt.%<SiO2≤13wt.%, 6wt.%<Na2O≤12wt.%, 1wt.%<SO3≤6wt.%, 1wt.%<CuO≤6wt.%.
[0040] As an example, in order to achieve the chemical composition requirements of the above-mentioned "S1# material", it can be achieved by limiting the purity and chemical composition of ulexite, colemanite, sylvasite and chalcanthite, that is, the selection of ulexite, colemanite, sylvasite and chalcanthite materials. Specifically, the purity requirement of ulexite is ≥90wt.%, and its chemical composition requirements are: Na2O>6wt.%, CaO>12wt.%, B2O3>38wt.%; the purity requirement of colemanite is ≥90wt.%, and its chemical composition requirements are: CaO>18wt.%, B2O3>33wt.%; the purity requirement of sylvasite is ≥90wt.%, and its chemical composition requirements are: Na2O>22wt.%, SiO2>42wt.%, B2O3>24wt.%; the purity requirement of chalcanthite is ≥90wt.%, and its chemical composition requirements are: CuO>28wt.%, SO3>28wt.%.
[0041] In this embodiment, when preparing "S1# material", the plating solution used is composed of anhydrous ethanol, phenolic resin, polymethyl methacrylate, dimethyl phthalate and diethyl phthalate. By mass ratio, anhydrous ethanol: phenolic resin: polymethyl methacrylate: dimethyl phthalate: diethyl phthalate = 65:15:10:5:5.
[0042] The formula of "S1# cement slurry system" matched with "S1# material" is: 100 parts by weight of G-grade high-resistance cement + 10 parts by weight of "S1# material" + 40 parts by weight of quartz sand + 9 parts by weight of relatively high-temperature terroir + 3 parts by weight of high-temperature stabilizer (ultrafine material and clay-like substance) + 6 parts by weight of high-temperature fluid loss reducer (AMPS-VP-AM-AA tetrapolymer) + 2 parts by weight of high-temperature retarder (AMPS-itaconic acid copolymer) + 65 parts by weight of water.
[0043] Example 2 As another preferred embodiment of the present invention, this embodiment discloses a cementing slurry anti-abnormal gelling material, which includes the following components by weight: 40 parts of ulexite, 35 parts of colemanite, 20 parts of sylvite and 5 parts of chalcanthite.
[0044] In this embodiment, the above-mentioned cement slurry abnormal gelling prevention material is prepared by the following preparation method: S1. 40 parts by weight of ulexite, 35 parts by weight of colemanite and 20 parts by weight of sylvite are mixed evenly, and then crushed by a grinding mill, with the crushing ratio controlled at 65; the crushed mixed material is sent to a ball mill for grinding into a mixed fine material, with the crushing ratio controlled at 750; then the crushed mixed fine material is sent to a high-temperature calcining furnace for calcination, with the calcination temperature controlled at 1200°C, and the calcined mixed material is quickly cooled to room temperature by a cooler, and the cooling time is controlled at 15min to obtain a Class A mixed material.
[0045] S2. Mix the Class A mixture prepared in step S1 with 5 parts by weight of gallstones and send it to a ball mill for grinding. After grinding, a Class B mixture is obtained; the particle size requirements of the Class B mixture are Dx(10)≤5μm, Dx(50)≤14μm, and Dx(90)≤30μm.
[0046] S3. The Class B mixture is subjected to coating treatment, specifically, 100 parts by weight of the Class B mixture is added to 1000 parts by weight of a 75wt.% coating solution, mixed evenly and reacted for 10 minutes, and then placed in a 40°C vacuum drying oven for drying to obtain the cement slurry anti-abnormal gelling material, referred to as "S2# material".
[0047] The chemical composition requirements of the above-mentioned "S2# material" are: 37wt.%<B2O3≤55wt.%, 11wt.%<CaO≤21wt.%, 5wt.%<SiO2≤13wt.%, 6wt.%<Na2O≤12wt.%, 1wt.%<SO3≤6wt.%, 1wt.%<CuO≤6wt.%.
[0048] As an example, in order to achieve the chemical composition requirements of the above-mentioned "S2# material", it can be achieved by limiting the purity and chemical composition of ulexite, colemanite, sylvasite and chalcanthite, that is, the selection of ulexite, colemanite, sylvasite and chalcanthite materials. Specifically, the purity requirement of ulexite is ≥90wt.%, and its chemical composition requirements are: Na2O>6wt.%, CaO>12wt.%, B2O3>38wt.%; the purity requirement of colemanite is ≥90wt.%, and its chemical composition requirements are: CaO>18wt.%, B2O3>33wt.%; the purity requirement of sylvasite is ≥90wt.%, and its chemical composition requirements are: Na2O>22wt.%, SiO2>42wt.%, B2O3>24wt.%; the purity requirement of chalcanthite is ≥90wt.%, and its chemical composition requirements are: CuO>28wt.%, SO3>28wt.%.
[0049] In this embodiment, when preparing "S2# material", the plating solution used is composed of anhydrous ethanol, phenolic resin, polymethyl methacrylate, dimethyl phthalate and diethyl phthalate. By mass ratio, anhydrous ethanol: phenolic resin: polymethyl methacrylate: dimethyl phthalate: diethyl phthalate = 55:20:8:10:7.
[0050] The formula of "S2# cement slurry system" matched with "S2# material" is: 100 parts by weight of G-grade high-resistance cement + 10 parts by weight of "S2# material" + 40 parts by weight of quartz sand + 9 parts by weight of relatively high-temperature terroir + 3 parts by weight of high-temperature stabilizer (ultrafine material and clay-like substance) + 6 parts by weight of high-temperature fluid loss reducer (AMPS-VP-AM-AA tetrapolymer) + 2 parts by weight of high-temperature retarder (AMPS-itaconic acid copolymer) + 65 parts by weight of water.
[0051] Example 3 As another preferred embodiment of the present invention, this embodiment discloses a cementing slurry anti-abnormal gelling material, which includes the following components by weight: 40 parts of ulexite, 35 parts of colemanite, 10 parts of ulexite and 15 parts of chalcanthite.
[0052] In this embodiment, the above-mentioned cement slurry abnormal gelling prevention material is prepared by the following preparation method: S1. 40 parts by weight of ulexite, 35 parts by weight of colemanite and 10 parts by weight of sylvite are mixed evenly, and then crushed by a grinding mill, with the crushing ratio controlled at 70; the crushed mixed material is sent to a ball mill for grinding into a mixed fine material, with the crushing ratio controlled at 800; then the crushed mixed fine material is sent to a high-temperature calcining furnace for calcining, with the calcining temperature controlled at 1000°C, and the calcined mixed material is quickly cooled to room temperature by a cooler, with the cooling time controlled at 10min, to obtain a Class A mixed material.
[0053] S2. Mix the Class A mixture prepared in step S1 with 15 parts by weight of gallstones, and then send it to a ball mill for grinding to obtain a Class B mixture. The particle size requirements of the Class B mixture are Dx(10)≤5μm, Dx(50)≤14μm, and Dx(90)≤30μm.
[0054] S3. The Class B mixture is subjected to coating treatment. Specifically, 100 parts by weight of the Class B mixture is added to 1500 parts by weight of a 70wt.% coating solution, mixed evenly and reacted for 15 minutes, and then placed in a 45°C vacuum drying oven for drying to obtain the cement slurry anti-abnormal gelling material, referred to as "S3# material".
[0055] The chemical composition requirements of the above-mentioned "S3# material" are: 37wt.%<B2O3≤55wt.%, 11wt.%<CaO≤21wt.%, 5wt.%<SiO2≤13wt.%, 6wt.%<Na2O≤12wt.%, 1wt.%<SO3≤6wt.%, 1wt.%<CuO≤6wt.%.
[0056] As an example, in order to achieve the chemical composition requirements of the above-mentioned "S3# material", it can be achieved by limiting the purity and chemical composition of ulexite, colemanite, sylvasite and chalcanthite, that is, the selection of ulexite, colemanite, sylvasite and chalcanthite materials. Specifically, the purity requirement of ulexite is ≥90wt.%, and its chemical composition requirements are: Na2O>6wt.%, CaO>12wt.%, B2O3>38wt.%; the purity requirement of colemanite is ≥90wt.%, and its chemical composition requirements are: CaO>18wt.%, B2O3>33wt.%; the purity requirement of sylvasite is ≥90wt.%, and its chemical composition requirements are: Na2O>22wt.%, SiO2>42wt.%, B2O3>24wt.%; the purity requirement of chalcanthite is ≥90wt.%, and its chemical composition requirements are: CuO>28wt.%, SO3>28wt.%.
[0057] In this embodiment, when preparing "S3# material", the plating solution used is composed of anhydrous ethanol, phenolic resin, polymethyl methacrylate, dimethyl phthalate and diethyl phthalate. By mass ratio, anhydrous ethanol: phenolic resin: polymethyl methacrylate: dimethyl phthalate: diethyl phthalate = 55:25:10:5:5.
[0058] The formula of "S3# cement slurry system" matched with "S3# material" is: 100 parts by weight of G-grade high-resistance cement + 10 parts by weight of "S3# material" + 40 parts by weight of quartz sand + 9 parts by weight of relatively high-temperature terroir + 3 parts by weight of high-temperature stabilizer (ultrafine material and clay-like substance) + 6 parts by weight of high-temperature fluid loss reducer (AMPS-VP-AM-AA tetrapolymer) + 2 parts by weight of high-temperature retarder (AMPS-itaconic acid copolymer) + 65 parts by weight of water.
[0059] Example 4 As another preferred embodiment of the present invention, this embodiment discloses a cementing slurry anti-abnormal gelling material, which includes the following components by weight: 50 parts of ulexite, 20 parts of colemanite, 15 parts of ulexite and 15 parts of chalcanthite.
[0060] In this embodiment, the above-mentioned cement slurry abnormal gelling prevention material is prepared by the following preparation method: S1. 50 parts by weight of ulexite, 20 parts by weight of colemanite and 15 parts by weight of sylvite are mixed evenly, and then crushed by a grinding mill, with the crushing ratio controlled at 40; the crushed mixed material is sent to a ball mill for grinding into a mixed fine material, with the crushing ratio controlled at 400; then the crushed mixed fine material is sent to a high-temperature calcining furnace for calcining, with the calcining temperature controlled at 800°C, and the calcined mixed material is quickly cooled to room temperature by a cooler, and the cooling time is controlled at 10min to obtain a Class A mixed material.
[0061] S2. Mix the Class A mixture prepared in step S1 with 15 parts by weight of gallstones, and then send it to a ball mill for grinding to obtain a Class B mixture. The particle size requirements of the Class B mixture are Dx(10)≤5μm, Dx(50)≤14μm, and Dx(90)≤30μm.
[0062] S3. The Class B mixture is subjected to coating treatment, specifically, 100 parts by weight of the Class B mixture is added to 2000 parts by weight of a 55wt.% coating solution, mixed evenly and reacted for 25 minutes, and then placed in a 50°C vacuum drying oven for drying to obtain the cement slurry anti-abnormal gelling material, referred to as "S4# material".
[0063] The chemical composition requirements of the above-mentioned "S4# material" are: 37wt.%<B2O3≤55wt.%, 11wt.%<CaO≤21wt.%, 5wt.%<SiO2≤13wt.%, 6wt.%<Na2O≤12wt.%, 1wt.%<SO3≤6wt.%, 1wt.%<CuO≤6wt.%.
[0064] As an example, in order to achieve the chemical composition requirements of the above-mentioned "S4# material", it can be achieved by limiting the purity and chemical composition of ulexite, colemanite, sylvasite and chalcanthite, that is, the selection of ulexite, colemanite, sylvasite and chalcanthite materials. Specifically, the purity requirement of ulexite is ≥90wt.%, and its chemical composition requirements are: Na2O>6wt.%, CaO>12wt.%, B2O3>38wt.%; the purity requirement of colemanite is ≥90wt.%, and its chemical composition requirements are: CaO>18wt.%, B2O3>33wt.%; the purity requirement of sylvasite is ≥90wt.%, and its chemical composition requirements are: Na2O>22wt.%, SiO2>42wt.%, B2O3>24wt.%; the purity requirement of chalcanthite is ≥90wt.%, and its chemical composition requirements are: CuO>28wt.%, SO3>28wt.%.
[0065] In this embodiment, when preparing "S4# material", the plating solution used is composed of anhydrous ethanol, phenolic resin, polymethyl methacrylate, dimethyl phthalate and diethyl phthalate. By mass ratio, anhydrous ethanol: phenolic resin: polymethyl methacrylate: dimethyl phthalate: diethyl phthalate = 70:15:5:5:5.
[0066] The formula of "S4# cement slurry system" matched with "S4# material" is: 100 parts by weight of G-grade high-resistance cement + 10 parts by weight of "S4# material" + 40 parts by weight of quartz sand + 9 parts by weight of relatively high-temperature terroir + 3 parts by weight of high-temperature stabilizer (ultrafine material and clay-like substance) + 6 parts by weight of high-temperature fluid loss reducer (AMPS-VP-AM-AA tetrapolymer) + 2 parts by weight of high-temperature retarder (AMPS-itaconic acid copolymer) + 65 parts by weight of water.
[0067] Example 5 As another preferred embodiment of the present invention, this embodiment discloses a cementing slurry anti-abnormal gelling material, which includes the following components by weight: 40 parts of ulexite, 40 parts of colemanite, 10 parts of sylvite and 10 parts of chalcanthite.
[0068] In this embodiment, the above-mentioned cement slurry abnormal gelling prevention material is prepared by the following preparation method: S1. 40 parts by weight of ulexite, 40 parts by weight of colemanite and 10 parts by weight of sylvite are mixed evenly, and then crushed by a grinding mill, with the crushing ratio controlled at 50; the crushed mixed material is sent to a ball mill for grinding into a mixed fine material, and the crushing ratio is controlled at 900; then the crushed mixed fine material is sent to a high-temperature calcining furnace for calcining, and the calcining temperature is controlled at 1500°C. After the calcination, the mixed material is quickly cooled to room temperature by a cooler, and the cooling time is controlled at 20min to obtain a Class A mixed material.
[0069] S2. Mix the Class A mixture prepared in step S1 with 10 parts by weight of gallstones and send it to a ball mill for grinding to obtain a Class B mixture. The particle size requirements of the Class B mixture are Dx(10)≤5μm, Dx(50)≤14μm, and Dx(90)≤30μm.
[0070] S3. The Class B mixture is subjected to coating treatment. Specifically, 100 parts by weight of the Class B mixture is added to 1500 parts by weight of a coating solution having a concentration of 85wt.%, mixed evenly and reacted for 35 minutes, and then placed in a 55°C vacuum drying oven for drying to obtain the cement slurry anti-abnormal gelling material, referred to as "S5# material".
[0071] The chemical composition requirements of the above-mentioned "S5# material" are: 37wt.%<B2O3≤55wt.%, 11wt.%<CaO≤21wt.%, 5wt.%<SiO2≤13wt.%, 6wt.%<Na2O≤12wt.%, 1wt.%<SO3≤6wt.%, 1wt.%<CuO≤6wt.%.
[0072] As an example, in order to achieve the chemical composition requirements of the above-mentioned "S5# material", it can be achieved by limiting the purity and chemical composition of ulexite, colemanite, ulexite and chalcanthite, that is, the selection of ulexite, colemanite, ulexite and chalcanthite materials. Specifically, the purity requirement of ulexite is ≥90wt.%, and its chemical composition requirements are: Na2O>6wt.%, CaO>12wt.%, B2O3>38wt.%; the purity requirement of colemanite is ≥90wt.%, and its chemical composition requirements are: CaO>18wt.%, B2O3>33wt.%; the purity requirement of ulexite is ≥90wt.%, and its chemical composition requirements are: Na2O>22wt.%, SiO2>42wt.%, B2O3>24wt.%; the purity requirement of chalcanthite is ≥90wt.%, and its chemical composition requirements are: CuO>28wt.%, SO3>28wt.%.
[0073] In this embodiment, when preparing "S5# material", the plating solution used is composed of anhydrous ethanol, phenolic resin, polymethyl methacrylate, dimethyl phthalate and diethyl phthalate. By mass ratio, anhydrous ethanol: phenolic resin: polymethyl methacrylate: dimethyl phthalate: diethyl phthalate = 60:15:8:7:10.
[0074] The formula of "S5# cement slurry system" matched with "S5# material" is: 100 parts by weight of G-grade high-resistance cement + 10 parts by weight of "S5# material" + 40 parts by weight of quartz sand + 9 parts by weight of relatively high-temperature terroir + 3 parts by weight of high-temperature stabilizer (ultrafine material and clay-like substance) + 6 parts by weight of high-temperature fluid loss reducer (AMPS-VP-AM-AA tetrapolymer) + 2 parts by weight of high-temperature retarder (AMPS-itaconic acid copolymer) + 65 parts by weight of water.
[0075] Comparative Example 1 Compared with Example 1, the cement slurry system in this comparative example does not add "S1# material", and the matching "D1# cement slurry system" formula is: 100 parts by weight of grade G high-resistance cement + 40 parts by weight of quartz sand + 9 parts by weight of relatively high-temperature terroir + 3 parts by weight of high-temperature stabilizer (ultrafine material and clay-like substance) + 6 parts by weight of high-temperature fluid loss reducer (AMPS-VP-AM-AA tetrapolymer) + 2 parts by weight of high-temperature retarder (AMPS-itaconic acid copolymer) + 65 parts by weight of water.
[0076] Comparative Example 2 Compared with Example 2, this comparative example does not undergo calcination and cooling processes, and the other conditions are the same. The abnormal gelling material for preventing cement slurry from setting in ultra-deep wells of 10,000 meters prepared in this comparative example is referred to as "D2# material".
[0077] The “D2# cement slurry system” that matches the “D2# material” is the same as the “S2# cement slurry system”.
[0078] Comparative Example 3 Compared with Example 3, this comparative example does not undergo coating treatment, and the other conditions are the same. The abnormal gelling prevention material for cement slurry used for ultra-deep well cementing in 10,000-meter wells prepared in this comparative example is referred to as "D3# material".
[0079] The “D3# cement slurry system” that matches the “D3# material” is the same as the “S3# cement slurry system”.
[0080] Comparative Example 4 Compared with Example 4, the components of the abnormal prevention gelling material in this comparative example are changed. The abnormal prevention gelling material includes the following components by weight: 20 parts of ulexite, 10 parts of colemanite, 5 parts of ulexite and 65 parts of chalcanthite. The chemical composition of the abnormal prevention gelling material exceeds the limited range in Example 4, and the other conditions are the same. The abnormal prevention gelling material for cement slurry for ultra-deep well cementing of 10,000 meters prepared in this comparative example is referred to as "D4# material".
[0081] The “D4# cement slurry system” that matches the “D4# material” is the same as the “S4# cement slurry system”.
[0082] Comparative Example 5 Compared with Example 5, the particle fineness of the anti-abnormal cementing material in this comparative example is changed, and the particle fineness of the anti-abnormal cementing material exceeds the limited range in Example 5, and the other conditions are the same. The anti-abnormal cementing material for cement slurry for ultra-deep wells of 10,000 meters prepared in this comparative example is referred to as "D5# material".
[0083] The “D5# cement slurry system” that matches the “D5# material” is the same as the “S5# cement slurry system”.
[0084] According to GB / T 19139-2012 standard, the engineering properties and mechanical properties of the cement slurry systems obtained in Examples 1 to 5 and Comparative Examples 1 to 5 were tested. The test results are shown in Table 1.
[0085] Table 1 Test results of engineering properties and mechanical properties of high temperature cementing cement Note: The curing conditions for the upper and lower density difference experiment are: 230℃×20.7MPa×48h, the free liquid content test conditions are: 90℃×0.1MPa×2h, the API water loss test conditions are: 185℃×6.9MPa×30min, the cement paste compressive strength curing conditions are: 230℃×20.7MPa, and the thickening test conditions are: 185℃×100MPa×100min.
[0086] It can be seen from the engineering performance test results in Table 1 that the cementing slurry system prepared in Examples 1 to 5 of the present invention has the advantages of good fluidity, zero free liquid content, low API water loss, good sedimentation stability, no abnormal gelation phenomenon during thickening, etc., and all meet the requirements of the high-temperature cement cement industry standards. In addition, the anti-abnormal gelling material for cementing slurry for ultra-deep wells of 10,000 meters in the present invention has good compatibility with high-temperature stabilizers, high-temperature fluid loss reducers, high-temperature retarders, etc. Compared with the blank sample (Comparative Example 1), the anti-abnormal gelling material of the present invention has little effect on the fluidity, free liquid, API water loss, sedimentation stability, etc. of the cement slurry system, and can greatly improve the abnormal gelation phenomenon during the thickening process of the cement slurry, and can be well applied in the high-temperature cementing slurry system.
[0087] It can be seen from the mechanical property test results in Table 1 that the cement paste formed by curing the cement slurry system prepared in Examples 1 to 5 of the present invention has the advantages of high compressive strength at high temperature and no decay. Compared with the blank sample (Comparative Example 1), the compressive strength of the cement paste at 2d and 7d is improved, indicating that the anti-abnormal cementitious material of the present invention can improve the density of the cement paste and has a beneficial effect on the compressive strength of the cement paste at high temperature.
[0088] Refer to the instruction manual Figure 1 and attached Figure 2 As shown, compared with Example 1, the cementing cement slurry system prepared in Comparative Example 1 exhibits serious abnormal gelation during the thickening process, which is specifically manifested as: the linear mutation value of the consistency exceeds 10Bc (obvious bulge appears on the curve), and the temperature curve fluctuates severely (obvious core coating appears on the thickening blade), indicating that the cement slurry system without adding the anti-abnormal gelling material of the present invention is difficult to ensure the stability of the high-temperature cement slurry thickening performance, thereby affecting the safety of cementing construction.
[0089] Refer to the instruction manual Figure 3 and attached Figure 4As shown, compared with Example 2, the cementing cement slurry system prepared in Comparative Example 2 exhibits serious abnormal gelation during the thickening process, which is specifically manifested as: the linear mutation value of the consistency exceeds 10Bc (obvious bulge appears on the curve), and the temperature curve fluctuates severely (obvious core coating appears on the thickening blade), indicating that the anti-abnormal gelation material prepared without calcination and cooling process cannot solve the abnormal gelation problem of high-temperature cement slurry thickening, which further illustrates the importance of each preparation process link of the anti-abnormal gelation material for ensuring the stable thickening performance of high-temperature cement slurry.
[0090] Refer to the instruction manual Figure 5 and attached Figure 6 As shown, compared with Example 3, the cementing slurry system prepared in Comparative Example 3 exhibited serious abnormal gelation during the thickening process, which was specifically manifested as follows: the linear mutation value of the consistency in the early stage of thickening exceeded 10Bc (obvious bulge appeared on the curve), and the other phenomena were normal (normal temperature curve, no core appeared on the thickening blade), indicating that the anti-abnormal gelling material that has not been coated cannot solve the problem of thickening bulge of high-temperature cement slurry. This is because the sulfate component in the anti-abnormal gelling material that has not been coated will undergo hydrolysis reaction, and the sulfate ions released under low temperature conditions will react with the aluminum ions and calcium ions in the cement slurry to generate stable calcium sulfonate and consume a large amount of water. At the same time, the needle-shaped calcium sulfonate interspersed and interlaced with each other, which easily caused the cement slurry to thicken rapidly in a short time, seriously affecting the safety of cementing construction. It shows that coating treatment is crucial for the anti-abnormal gelling material to ensure the stability of the thickening performance of high-temperature cement slurry.
[0091] Refer to the instruction manual Figure 7 and attached Figure 8 As shown, compared with Example 4, the cementing cement slurry system prepared in Comparative Example 4 exhibits serious abnormal gelation during the thickening process, which is specifically manifested as: the linear mutation value of the consistency exceeds 10Bc (obvious bulge appears on the curve), and the temperature curve fluctuates severely (obvious core wrapping appears on the thickening blade), indicating that when the chemical composition of the anti-abnormal gelling material exceeds the specified range of the present invention, the abnormal gelling problem of high-temperature cement slurry thickening cannot be solved. Further, it is explained that only by meeting the chemical composition requirements of the anti-abnormal gelling material of the present invention can the corresponding performance be achieved and the problem raised in the present application be solved. This is because the anti-abnormal gelling material of the present invention is a chemical component ratio specially designed for the abnormal gelling phenomenon of cement slurry, and each component can exert the best performance of the material within this specified range.
[0092] Refer to the instruction manual Fig. 9 and attached Fig.10As shown, compared with Example 5, the cementing slurry system prepared in Comparative Example 5 exhibits serious abnormal gelation during the thickening process, which is specifically manifested as: the linear mutation value of the consistency exceeds 10Bc (obvious bulge appears on the curve), and the temperature curve fluctuates severely (obvious core wrapping appears on the thickening blade), indicating that when the particle fineness of the anti-abnormal gelling material exceeds the specified range of the present invention, the abnormal gelation problem of high-temperature cement slurry thickening cannot be solved, and further indicating that only by meeting the particle fineness requirements of the anti-abnormal gelling material of the present invention can the corresponding performance be achieved and the problem raised in the present application be solved. This is because when the anti-abnormal gelling material is too fine, it will lead to abnormal gelation and performance conflict with other admixtures. In addition, if the material is too fine, its solubility will be accelerated, and water absorption too quickly will easily cause cement slurry to thicken, which is not conducive to construction safety; when the anti-abnormal gelling material is too coarse, its solubility will deteriorate, and the performance of the material cannot be exerted in time. In addition, if the material is too coarse, sedimentation will occur, thereby affecting the stability of the material. Therefore, as long as the particle fineness requirement exceeds this range, the performance of the material will be hindered, so it is necessary to limit the fineness of the material of this application.
[0093] Example 6 As another preferred embodiment of the present invention, this embodiment discloses the application of the anti-abnormal gelling material of cementing slurry in the above-mentioned embodiments 1 to 5 in cementing slurry of ultra-deep wells of 10,000 meters. It is used to inhibit the abnormal gelling of cementing slurry of ultra-deep wells of 10,000 meters. From the perspective of cement hydration products, it solves the abnormal gelling effect of cement slurry caused by fluctuations in cement mineral components under different batches.
[0094] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention to illustrate the technical solutions of the present invention, rather than limiting them, and certainly not limiting the patent scope of the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. In other words, any changes or modifications made to the main design concept and spirit of the present invention that have no substantive significance, and the technical problems they solve are still consistent with the present invention, should be included in the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention in other related technical fields is also included in the patent protection scope of the present invention.
Claims
1. Cementing slurry anti-abnormal gelling material, characterized by: The composition comprises the following components in parts by weight: 40-60 parts of ulexite; 20-40 parts of colemanite; 10-20 parts of pyrophyllite; 5-15 parts of gallstones; The chemical composition requirements of the abnormal gelling material for cementing slurry are: 37wt.%<B2O3≤55wt.%, 11wt.%<CaO≤21wt.%, 5wt.%<SiO2≤13wt.%, 6wt.%<Na2O≤12wt.%, 1wt.%<SO3≤6wt.%, 1wt.%<CuO≤6wt.%; the particle fineness requirements of the abnormal gelling material for cementing slurry are Dx(10)≤5μm, Dx(50)≤14μm, Dx(90)≤30μm.
2. The abnormal gelling prevention material for cementing slurry according to claim 1, characterized in that: The purity of the ulexite is required to be ≥90wt.%, and its chemical composition is required to be: Na2O>6wt.%, CaO>12wt.%, B2O3>38wt.%.
3. The abnormal gelling prevention material for cementing slurry according to claim 1, characterized in that: The purity of the colemanite is required to be ≥90wt.%, and the chemical composition requirements are: CaO>18wt.%, B2O3>33wt.%.
4. The abnormal gelling prevention material for cementing slurry according to claim 1, characterized in that: The purity of the sodium borosilicate is required to be ≥90wt.%, and its chemical composition requirements are: Na2O>22wt.%, SiO2>42wt.%, B2O3>24wt.%.
5. The abnormal gelling prevention material for cementing slurry according to claim 1, characterized in that: The purity of the gallstone is required to be ≥90wt.%, and its chemical composition is required to be: CuO>28wt.%, SO3>28wt.%.
6. The method for preparing the abnormal gelling prevention material for cementing slurry according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Mix 40-60 parts of ulexite, 20-40 parts of colemanite and 10-20 parts of boraxite evenly, crush them after mixing evenly, and control the crushing ratio to 40-70; grind the crushed mixed material into mixed fine material, and control the crushing ratio to 400-900; send the crushed mixed fine material to a high-temperature calcining furnace for calcination, and control the calcination temperature to 800°C-1500°C; the mixed material after calcination is quickly cooled to room temperature, and the cooling time is controlled to 10-20min; after cooling, obtain Class A mixed material; S2, mixing the Class A mixture prepared in step S1 with 5-15 parts of gallstones, and grinding the mixture to obtain a Class B mixture; the particle size requirements of the Class B mixture are Dx(10)≤5μm, Dx(50)≤14μm, and Dx(90)≤30μm; S3, subjecting the Class B mixture to a coating treatment, specifically, adding the Class B mixture to a coating solution, mixing evenly and reacting for a set time, and vacuum drying to obtain the cement slurry anti-abnormal gelling material.
7. The method for preparing the abnormal gelling prevention material for cementing slurry according to claim 6, characterized in that: The coating solution comprises the following components by mass ratio: Anhydrous ethanol: phenolic resin: polymethyl methacrylate: dimethyl phthalate: diethyl phthalate = (55~70): (15~25): (5~10): (5~10): (5~10).
8. The method for preparing the abnormal gelling prevention material for cementing slurry according to claim 6 or 7, characterized in that: The concentration of the plating solution is 55wt.% to 85wt.%.
9. The method for preparing the abnormal gelling prevention material for cementing slurry according to claim 6 or 7, characterized in that: In step S3, the dosage ratio of the type B mixture to the coating solution is 1:(5~20).
10. The method for preparing the abnormal gelling prevention material for cementing slurry according to claim 6 or 7, characterized in that: In step S3, the reaction time is set to 5 to 35 minutes.
11. The method for preparing the abnormal gelling prevention material for cementing slurry according to claim 6 or 7, characterized in that: In step S3, the vacuum drying temperature is 35°C to 55°C.
12. Application of the abnormal gelling material for cementing slurry as claimed in any one of claims 1 to 5 in cementing slurry for ultra-deep wells with a depth of 10,000 meters.
Citation Information
Patent Citations
Medium-high-temperature oil well cement retarding agent as well as preparation method and application thereof
CN109503760A
High-temperature oil well cement retarder capable of inhibiting abnormal gelling, and preparation method thereof
CN111662409A
Multistage adsorption polymer fluid loss agent and preparation method thereof
CN114292634A
Fluid loss agent for inhibiting early abnormal gelling of cement paste and preparation method thereof
CN114805706A
High-temperature-resistant energy-saving insulation board for industrial furnace and preparation method
CN112898043A